Riba and Interest in The View Of The Four Madzhab and Contemporary Ulama - Munir Munir; Ahmad Adil Manan; Shofa Robbani; Ahmad Munir (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The discourse on usury is a classic issue, both in the development of Islamic thought and in Islamic civilization. Riba is a complicated problem that often occurs in society. The research focus that forms the basis for this research is (1) What are the opinions of the 4 madzhab scholars regarding usury? (2) What are the opinions of contemporary scholars about bank interest?, and the purpose of this research is (1) to find out what the opinions of 4 madhhab scholars about usury are, (2) to find out what contemporary scholars think about bank interest. This research is a type of library research. The results of this study are that the opinion of the Hanafi Madzhab regarding the sale and purchase of goods that are exchanged or weighed with usury goods if they are weighed for trading and there is an addition, it can be said that usury fadhl. The opinion of the Maliki school of illat usury is when usury goods are used as a price. According to the opinion of the Shafi'i Madhhab, illat usury focuses on usury goods when they become the value of the price, if the two goods are valued or become the price of something. While illat on food is anything that can be eaten and fulfills several criteria such as food or staple food, according to the Hambali Madzhab what can be said is usury is every sale and purchase of a kind that is weighed with one date. Bank interest according to the opinion of contemporary scholars, namely KH. Sahal Madfudh explained about the exploitative, inhuman and consumptive nature of bank interest. Therefore, the concept of bank interest for productive behavior for people's business according to kyai sahal is permissible. Meanwhile, bank interest for consumptive and unproductive behavior is prohibited. According to M. Quraish Shihab, bank interest is not illegal, considering that the current interest does not contain elements of persecution and oppression among human beings. According to him, it does not prohibit bank interest because there are still scholars who allow it, because the interest has been agreed upon at the beginning of the transaction and does not contain elements of oppression and persecution, but if you want to be safe, you should make transactions at Islamic banks. Yusuf Al-Qardhawi said that bank interest taken by savers at the bank is usury which is forbidden, Yusuf Qardhawi firmly stated that bank interest is the same as usury which will always be punished as haram.